Analysis of Genotypes and Phenotypes in Chinese Patients With Tuberous Sclerosis Complex Harboring Novel Variants of TSC1 and TSC2 Genes - Jian Chen; Hairui Sun; Ling Han; Xiaoyan Gu; Xiaoyan Hao; Yuwei Fu; Zongjie Weng; Yi Xiong; Baomin Liu; Hongjia Zhang; Yihua He; Hong Li (International Journal of Genomics)
Conclusions: This study broadens the spectrum of variants of TSC1 and TSC2 genes, reaffirming the clinical diagnosis of patients through genetic testing.